What more than parental income? An exploration of what Swedish siblings get from their parents - Anders Björklund; Lena Lindahl; Matthew J. Lindquist (Institute for the Study of Labor (IZA), 2008)
Sibling correlations are used as overall measures of the impact of family background and community influences on individual outcomes. While most correlation studies show that siblings are quite similar in terms of future achievement, we lack specific knowledge of what it is about family background that really matters. Studies on intergenerational income mobility show that parental income matters to some extent, but they also show that more than half of the family background and community influences that siblings share are not even correlated with parental income. In this paper, we employ a data set that contains rich information about families in order to explore what factors in addition to parental income can explain why siblings tend to have such similar outcomes. Our results show that measures of family structure and social problems account for very little of sibling similarities in adult income above and beyond that already accounted for by parental income. However, when we add a set of indicators for parental involvement and attitudes, the explanatory power of all our variables increased from about a third (using only traditional indicators of socio-economic status) to just over half. Interestingly, indicators of parents' patience, i.e., propensity to plan ahead and willingness to postpone benefits to the future, are particularly important.
urn:nbn:de:101:1-2008101500
Keywords: D1; 330; Family background; intergenerational mobility; parents; siblings; long-run income; Soziale Mobilität; Generationenbeziehungen; Familiensoziologie; Lebenseinkommen; Schweden